An Action Inquiry to Develop a Marking Guide for Poster Presentations by Undergraduate Nursing Students - McMullan, Johanna (International Journal of Innovative Research in Medical Science, 2018)
The aim of this paper is to explore the process of an action inquiry approach to produce a mark guide for a poster presentation assessment undertaken by undergraduate student nurses. Historically students have failed to engage with the task of poster presentation as they were of the opinion that the marks awarded by tutors failed to reflect the effort or skills acquired in completing the task. To solve this problem firstly the effort and skills required whilst completing the task must be captured. Secondly these must be accurately translated into a robust mark guide. The overall outcome will hopefully be a change in students’ attitude to engaging with poster presentation as an assessment method as they see a robust and accurate mark guide that accurately reflects the task carried out. In order for this change to occur and produce a desirable outcome it is imperative that the students have ownership of the project and are fully involved at every stage and this is why an action research methodology was employed.